KONSTRUKSI EKSISTENSI ISTRI PERTAMA DALAM FILM (ANALISIS SEMIOTIKA JOHN FISKE PADA FILM SURGA YANG TAK DIRINDUKAN) - Apriani Da Silva; Monika Wutun; Juan Ardiles Nafie (Jurnal Digital Media dan Relationship, 2022)
The main problem in this study is to describe the construction of the existence of the first wife in the unmissable paradise movie, the formulation of the problem is how the construction of the existence of the first wife before knowing her husband remarried, and how the construction of the existence of the first wife after knowing her husband remarried, as well as making comparisons between the two constructions. the existence. This study aims to describe how the first wife in the film describes the construction of her existence before and after knowing her husband remarried, and to compare the existence of the first wife before and after knowing her husband remarried. This study uses qualitative research with John Fiske's semiotic analysis method, which analyzes through three levels, namely the level of reality, the level of representation, and the level of ideology. The object of research consists of 8 scenes, including 3 scenes that describe the existence of the first wife before knowing her husband remarried, and 5 scenes that describe the existence of the first wife after knowing her husband remarried. Data collection techniques using observation and documentation. The results of the study show that in the unmissable paradise movie there are 3 forms of construction of the existence of the first wife before knowing her husband remarried including always thinking positive, afraid and anxious, and ideal and understanding housewives. While the construction of the existence of the first wife after knowing her husband remarried there are 3 forms including disappointment, toughness, and caring contained in 5 scenes.